PENINGKATAN KEMAMPUAN MOTORIK HALUS MELALUI KEGIATAN MELIPAT MENGGUNAKAN KERTAS ORIGAMI PADA ANAK KELOMPOK B TK PGRI DEWI ANJANI OTAK DESA JONGGAT - ROKYAL HARJANTY (Lembaga Penelitian dan Pendidikan Mandala, 2019)
This research is motivated by the results of the assessment of children's development, that there are 87% of 23 Group B children in TK PGRI Dewi Anjani Otak Desa that are still incomplete in the development of fine motor skills. The problem of this research is whether the application of folding activities using origami paper can improve children's fine motor skills. This research is a Classroom Action Research. The subjects were 23 children of Group B TK PGRI Dewi Anjani Otak Desa. The object of this research is fine motor skills using the Kemmis and Mc Taggart models. Data collection techniques are done using observation and assessment rubrics. The instrument used is the observation instrument sheet. The data analysis technique is quantitative descriptive. The established success indicator is 75% of 23 children have fine motor skills. This research was conducted in three cycles. The results showed that the completeness of children's fine motor learning in Cycle I was 35%, in Cycle II it was 61%, and in Cycle III it was 82%. The percentage acquisition in Cycle III proves that this study has reached an indicator of success, namely the fine motor skills of children has increased> 75%. Based on the results of the study it can be concluded that through this activity can improve fine motor skills in Group B children in TK PGRI Dewi Anjani Otak Desa.